Humanitarian cooperation as a factor in the strategic partnership between Russia and Germany - Natalie Iakovleva (European Regional Science Association (ERSA), 2014)
The main idia of the article is to describe the humanitarian relations of the Altai region and the federal Land of Saxony- Angalt. The item is to represent the difference of the meaning of such words as «humanitarian» and « humanitarian relations». The problem is that there are some differences in understanding of this type of cooperation. In European Union, «humanitarian collaboration» mean protection of human rights, the provision of emergency relief (food supply, rehabilitation of health services, mine soils etc.). But in Russia «humanitarian cooperation» and «humanitarian collaboration» has the same meaning and covers an area of cultural relations, inter-civilizational, civil society dialogue and relations with compatriots abroad. In this case it can play a «soft power» between the Germany and Russian cooperation and regional relations. In the development of regional cooperation between some Germany federal Lands and regions in Russia, author gives us example of such communication and describes the humanitarian relations between the Altai region and the federal Land of Saxony- Angalt. There is a German national region in Altai, which has its own territory, low and budget. People there can choose the school and language of education: Germany or Russian. So, in this article author wants to describe how to make strong political and economic relationship which is basic on cultural and humanitarian communication. The author give us brief information about the history of the in the Altai region, it's participation in joint projects with Germany, learning Germany language as a home language at the local and regional levels in German national region. For the regional development in Russia, existence of a common culture, ethnicity and friendly relations makes cooperation easier and beneficial. It's an example for other regions how to lead international activities and how to make the Regional economic growth up. Actually, this type of cooperation is one of the areas paradiplomacy and for today is a new phenomenon in Russia. And the example of the relations of the Altai region and the federal Land of Saxony- Angalt is an example of paradiplomacy in Europe and America. In this case, author gives us the meaning of such communication in Russia.
Keywords: 330